Haploid male germ cells—the Grand Central Station of protein transport. (21st April 2020) - Pleuger, Christiane; Lehti, Mari S; Dunleavy, Jessica EM; Fietz, Daniela; O'Bryan, Moira K
Abstract: BACKGROUND: The precise movement of proteins and vesicles is an essential ability for all eukaryotic cells. Nowhere is this more evident than during the remarkable transformation that occurs in spermiogenesis—the transformation of haploid round spermatids into sperm. These transformations are critically dependent upon both the microtubule and the actin cytoskeleton, and defects in these processes are thought to underpin a significant percentage of human male infertility. OBJECTIVE AND RATIONALE: This review is aimed at summarising and synthesising the current state of knowledge around protein/vesicle transport during haploid male germ cell development and identifying knowledge gaps and challenges for future research. To achieve this, we summarise the key discoveries related to protein transport using the mouse as a model system. Where relevant, we anchored these insights to knowledge in the field of human spermiogenesis and the causality of human male infertility. SEARCH METHODS: Relevant studies published in English were identified using PubMed using a range of search terms related to the core focus of the review—protein/vesicle transport, intra-flagellar transport, intra-manchette transport, Golgi, acrosome, manchette, axoneme, outer dense fibres and fibrous sheath. Searches were not restricted to a particular time frame or species although the emphasis within the review is on mammalian spermiogenesis. OUTCOMES: Spermiogenesis is the final phase of sperm development. It results in the transformation of a round cell into a highly polarised sperm with the capacity for fertility. It is critically dependent on the cytoskeleton and its ability to transport protein complexes and vesicles over long distances and often between distinct cytoplasmic compartments. The development of the acrosome covering the sperm head, the sperm tail within the ciliary lobe, the manchette and its role in sperm head shaping and protein transport into the tail, and the assembly of mitochondria into the mid-piece of sperm, may all be viewed as a series of overlapping and interconnected train tracks. Defects in this redistribution network lead to male infertility characterised by abnormal sperm morphology (teratozoospermia) and/or abnormal sperm motility (asthenozoospermia) and are likely to be causal of, or contribute to, a significant percentage of human male infertility. WIDER IMPLICATIONS: A greater understanding of the mechanisms of protein transport in spermiogenesis offers the potential to precisely diagnose cases of male infertility and to forecast implications for children conceived using gametes containing these mutations. The manipulation of these processes will offer opportunities for male-based contraceptive development. Further, as increasingly evidenced in the literature, we believe that the continuous and spatiotemporally restrained nature of spermiogenesis provides an outstanding model system to identify, and de-code, cytoskeletal elements and transport mechanisms of relevance to multiple tissues.